Revenge and/or Justice in Quentin Tarantino’s Film Inglourious Basterds - Mulyanto, Luke Zefanezra; Napitupulu, Johanes Claudio Perdana; Pasopati, Rommel Utungga; Hariyono, Hariyono; Wijaya, Kusuma (SALIENCE: English Language, Literature, and Education Journal, 2025)
This article describes the senses of revenge and/or justice in Inglourious Basterds, particularly through the characters of Shoshanna Dreyfus, Aldo Raine and the Basterds, and Hans Landa. Universal Pictures released this 2009 film directed by Quentin Tarantino. The writers of this article employ a qualitative method, which allows the reader to learn more about the object's background. These revenge and/or justice scenes describe how revenge and/or justice intertwine in this film. The characters play great actings by indicating that such retaliation is always meaningful, giving inner satisfaction but also contains such justice to the perpetrator. Taking revenge in this film then means as a tool to realize the best way to eliminate the roots of evil that is in line with realizing justice either. In conclusion, the senses of revenge and/or justice in Inglorious Basterds is interpreted flexibly by underlining the characters’ dialogues alongside the ambience of the Nazis’ deeds in World War II.